Pengaruh Content Marketing dan Online Customer Review terhadap Keputusan Pembelian dengan Customer Trust sebagai Variabel Intervening: (Studi customer TikTok Shop di Pati) - Septiana Aulia Febrianti; Heri Prabowo; Ira Setiawati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to reveal the influence of various factors in digital marketing on consumer purchases on the TikTok Shop platform. This study specifically aims to assess the impact of content marketing and online customer reviews on purchasing decisions with customer trust as an intervening variable on TikTok Shop customer in Pati. This study uses a quantitative method. The population studied was TikTok Shop consumers in the Pati area, with an unknown number. A total of 97 respondents were sampled through a non-probability sampling technique with a purposive sampling approach. Data analysis was carried out using SmartPls 3 software. The results of the study showed that content marketing had an influence on purchasing decisions, while online customer reviews did not have a significant influence. In addition, content marketing and online customer reviews had an effect on purchasing decisions. However, customer trust was not proven to influence purchasing decisions. Content marketing and online customer reviews also had no influence on purchasing decisions through customer trust as an intervening variable on TikTok Shop customer in Pati.